Navigating the Ethical Crossroads of Suicide Attempts and End-of-Life Directives - Nemetz, Elisheva; Huang, Ryan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Do Not Resuscitate (DNR) orders are intended to respect patient autonomy and prevent unnecessary suffering when resuscitative efforts are unlikely to provide meaningful benefit. While their use is well established in end-of-life care, their application becomes ethically and procedurally complex when a patient with an existing DNR order attempts suicide. This paper explores the challenges that arise in such cases, emphasizing the need for a nuanced approach that integrates clinical assessment, considers the temporal context of suicidal intent, and upholds foundational DNR principles.